Etnologija, etnografija ali narodopisje - Ferlež, Jerneja (Etnolog. Nova vrsta (Ljubljana), 2000)
The article presents a survey of the problems ethnologists and anthropologists encounter in libraries, and briefly presents some particularities of special ethnological terminology as well as different views on indexing with an emphasis on user-oriented keywords. The same issues are also elucidated by a survey held among ethnologists and nonethnologists, by question put forward by the users of the University of Maribor Library, and by a comparison of keywords used by individual libraries for indexing ethnologiocal material.
Keywords: ethnology; etnologija; kulturna antropologija; terminologija; terminology; knjižnice; bibliotekarstvo; library science; geslenje; uporabniki